Development of mobile application program to promote travel for the elderly in the city community to use healthcare services in Sirindhorn Hospital, Bangkok - Pastraporn Thipayasothorn; Amonchai Chaichana; Aueamaumporn Phetsinchorn; Thipawan Ruangrit; Pratum Munkong (My University, 2022)
Aging health circumstances combined with travel challenges in the city community of Sirinhorn hospital have a direct relation to the deteriorating health and environment of the elderly, which are generally based on a number of different old age-related diseases.Hence, this is the main reason for healthcare service provision to the elderly for enhanced life quality.In addition, a number of other broader factors such as the overall service system of hospitals, hospital accessibility, public transportation system, the elderly's private vehicles, and supportive technology for the elderly's travel to hospital can potentially impact their means to acquire hospital-based health services.Therefore, this two-fold research was conducted to develop a mobile application program to promote travel for the elderly in the city community, who currently seek health services at Sirindhorn hospital in Bangkok and to evaluate the developed mobile application program's effectiveness and efficiency in supporting the elderly's travel to hospital.The program development process involved specialists, experts and thirty elderly participants who pilot-tested the developed mobile application program for their travels to the hospital.Results showed that participants were satisfied with their experiences in using the developed application program, particularly through the convenience in giving and acquiring information on the application program that significantly supported their travels to the hospital.This study presented implications for public healthcare stakeholders in their provision of effective health services to the Thai elderly.
Keywords: Global Healthcare and Medical Tourism